2004
DOI: 10.1196/annals.1316.050
|View full text |Cite
|
Sign up to set email alerts
|

Possible Pharmacotherapy of the Opioid κ Receptor Agonist for Drug Dependence

Abstract: Because there are few efficacious medications for drug dependence, many clinical trials are being conducted in earnest to find such medications. Considerable evidence has shown that opioid kappa receptor agonists attenuate several behavioral responses induced by drugs of abuse. Although this raises the possibility that opioid kappa receptor agonists may be useful for the treatment of drug dependence on drugs of abuse, it has been previously reported that treatment with selective opioid kappa receptor agonists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 31 publications
(52 reference statements)
1
41
0
Order By: Relevance
“…Accordingly, both pharmacological and genetic studies have provided evidence that the rewarding effects of cannabinoids are mediated by the activation of m-opioid receptors, whereas the stimulation of k-opioid receptors (KORs) by opioid peptides derived from pro-dynorphin seem to mediate their aversive effects (Ghozland et al, 2002;Zimmer et al, 2001). Moreover, several studies suggest that the k/dynorphin system opposes drug-rewarding effects, giving support to the idea that KORs could act as a possible pharmacotherapy for drug dependence (for a review, see Hasebe et al, 2004). Thus, KORs inhibit the rewarding effects of several drugs of abuse, such as morphine or cocaine, and also attenuate the elevation of dopamine turnover induced by morphine in the limbic forebrain (Narita et al, 1993;Schenk et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, both pharmacological and genetic studies have provided evidence that the rewarding effects of cannabinoids are mediated by the activation of m-opioid receptors, whereas the stimulation of k-opioid receptors (KORs) by opioid peptides derived from pro-dynorphin seem to mediate their aversive effects (Ghozland et al, 2002;Zimmer et al, 2001). Moreover, several studies suggest that the k/dynorphin system opposes drug-rewarding effects, giving support to the idea that KORs could act as a possible pharmacotherapy for drug dependence (for a review, see Hasebe et al, 2004). Thus, KORs inhibit the rewarding effects of several drugs of abuse, such as morphine or cocaine, and also attenuate the elevation of dopamine turnover induced by morphine in the limbic forebrain (Narita et al, 1993;Schenk et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…b-Arrestins 1 and 2 are associated with ND D Sun et al roles in the opioid receptor and MAPK signaling transduction processes [24][25][26]46 and the extensive evidence that opioid receptors and MAPK cascades are involved in drug addiction, [18][19][20][21][22][27][28][29][30] ARRB1 and ARRB2 were considered plausible candidates for ND.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence has shown the opioid receptors play a central role in the development of drug abuse via the disinhibition of ventral tegmental area (VTA) dopaminergic neurons. [18][19][20][21] Previous reports indicated that the reinforcing properties of nicotine are strongly diminished in mice lacking the m-opioid receptor, 22 and acute nicotine administration increased the expression of m-opioid receptors in the VTA. 23 b-arrestins have been proven to be important regulators of signal transduction mediated by opioid receptors through promotion of receptor desensitization and internalization.…”
Section: Introductionmentioning
confidence: 99%
“…However, in humans it has been shown that activation of kappa opioid receptors acutely may cause dysphoria and psychotomimesis (Pfeiffer et al, 1986) and this limits the clinical usefulness of these drugs. Research to develop kappa-opioid receptor agonists that do not have the dysphoric properties is ongoing (Hasebe et al, 2004;Park et al, 2006). A better understanding of the systems involved in mediating the long-term effects of kappa-opioid receptor agonists on cocainestimulated locomotor activity will aid in the development of compounds that may be able to bypass the dysphoric properties associated with the currently available kappa receptor agonists while preserving the ability to block the effects of cocaine.…”
Section: Introductionmentioning
confidence: 99%